مصادر ضغوط العمل النفسية لدى معلمات الحلقة الثانية من التعليم الأساسي وعلاقتها ببعض المتغيرات "دراسة ميدانية في محافظة اللاذقية" (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
يهدف هذا البحث إلى التعرف إلى مصادر ضغوط العمل النفسية لدى معلمات الحلقة الثانية من التعليم الأساسي في محافظة اللاذقية, ولتحقيق أهداف البحث تمّ بناء استبانة, وتطبيقها على عينة من المعلمات بلغت /431/ معلمة, وانتهى البحث إلى النتائج التالية: 1- إن أكثر مصادر ضغوط العمل النفسية لدى معلمات الحلقة الثانية من التعليم الأساسي هو مجال البيئة المدرسية, يليه العلاقة مع مدير المدرسة, يليه العلاقة مع الطلاب, يليه العلاقة مع أولياء الأمور, يليه عبء العمل, يليه المناهج الدراسية. 2- وجود فروق ذات دلالة إحصائية بين متوسطات استجابات المعلمات تعزى لمتغير المؤهل العلمي, وهذه الفروق تعود للمؤهل العلمي معهد متوسط. 3- وجود فروق ذات دلالة إحصائية بين متوسطات استجابات المعلمات تعزى لمتغير عدد سنوات الخدمة, وهذه الفروق تعود لعدد سنوات الخدمة (أقل من 5 سنوات). 4- وجود فروق ذات دلالة إحصائية بين متوسطات استجابات المعلمات تعزى لمتغير الحالة الاجتماعية, وهذه الفروق تعود للمعلمات المتزوجات. This research aims at identifying the resources of psychological work stress for second stage female teachers of primary teaching in Lattakia. So to achieve the objectives of this research, a questionnaire has been designed and  applied to a sample of (431) female. The results are as follows: 1- The greatest psychological work tolerance for second stage female teachers of primary teaching is related to school environment, the relationship with the school principal of the, the relationship with pupils and parents, work tolerance, and school curricula. 2- Due to the  academic qualifications (Intermediate Institute), there are significant  statistical differences between the means of  female teachers'  responses. 3- Due to the years of experience variable (less than 5 years), there are significant statistical differences  between the means of female teachers' responses. 4- Due to the social conditions variable, there are significant statistical differences between the means of female teachers' responses (especially, married ones).